The Glycoproteins of Plant Seeds : ANALYSIS BY TWO-DIMENSIONAL POLYACRYLAMIDE GEL ELECTROPHORESIS AND BY THEIR LECTIN-BINDING PROPERTIES - Basha, Shaik-M. M. (1981)
Protein from the jack bean, peanut, soybean and kidney bean seeds were extracted with a solution containing 9.3 molar urea, 5 millimolar K(2)CO(3), 0.5% dithiothreitol and 2% Nonidet P-40 and then subjected to two-dimensional gel electrophoresis. After electrophoresis, the slab gels were stained with a variety of (125)I-labeled lectins and the lectin-binding proteins were identified after autoradiography. Incubation of slab gels of jack bean with concanavalin A, peanut with peanut agglutinin, soybean with soybean agglutinin, and kidney bean with phytohemagglutinin showed that the majority of the polypeptides in each seed type were able to bind to their homologous lectins. Control slab gels in which incubations were carried out with identical amounts of proteins, (125)I-lectin and an appropriate sugar inhibitor showed little or no lectin binding to the polypeptides. Additionally, incubation of slab gels of peanut proteins with (125)I-ricin, (125)I-wheat germ agglutinin, (125)I-concanavalin A, and (125)I-soybean agglutinin each revealed a clearly distinct binding pattern compared to the one observed with the peanut agglutinin. The results demonstrate that a large number of legume seed polypeptides are glycoproteins and that the carbohydrate groups within a seed species are heterogeneous in structure, thus indicating the existence of complex glycosylating enzyme systems in legume seeds. It is suggested that the high degree of binding between seed proteins and their homologous lectins might have some functional significance in maintaining large aggregates of protein in compact, insoluble form.